2014
DOI: 10.1146/annurev-nutr-071813-105817
|View full text |Cite
|
Sign up to set email alerts
|

Launching a New Food Product or Dietary Supplement in the United States: Industrial, Regulatory, and Nutritional Considerations

Abstract: Launching a new food/dietary supplement into the US market can be a confusing process to those unfamiliar with the food industry. Industry capability and product specifications are initial determinants of whether a candidate product can be manufactured in a reproducible manner and whether pilot production can be brought up to the market scale. Regulatory issues determine how a product can be produced and marketed; the primary federal institutions involved in regulations are the US Department of Agriculture, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Part of the challenge ahead for algal scientists is understanding the complexity of merging of basic research through clinical trials and regulatory requirements to create marine food products. The recent comprehensive reviews by Finley et al (2014) and Borowitzka (2013b) help to clarify this pathway. But the most dramatic advances will require a rethinking of experimental and collaborative approaches, and the impetus for this research will only increase as human pressures on the climate system lead us to turn more to the oceans for food that we can harvest and grow sustainably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the challenge ahead for algal scientists is understanding the complexity of merging of basic research through clinical trials and regulatory requirements to create marine food products. The recent comprehensive reviews by Finley et al (2014) and Borowitzka (2013b) help to clarify this pathway. But the most dramatic advances will require a rethinking of experimental and collaborative approaches, and the impetus for this research will only increase as human pressures on the climate system lead us to turn more to the oceans for food that we can harvest and grow sustainably.…”
Section: Discussionmentioning
confidence: 99%
“…The path from algal research to the launching of new food products or dietary supplements is strongly affected by industrial, regulatory, and nutritional considerations (e.g., see Borowitzka 2013a; Finley et al 2014). The widespread interest in algal foods and/or their functional food potential is evident in numerous recent reviews (Warrand 2006; MacArtain et al 2007; Kulshreshtha et al 2008; Bocanegra et al 2009; Mendes et al 2009; Cottin et al 2011; Harnedy and FitzGerald 2011; Holdt and Kraan 2011; Lordan et al 2011; Pangestuti and Kim 2011; Stengel et al 2011; Cornish et al 2015; Hafting et al 2015) and books (Rhatigan 2009; Mouritsen 2013; Tiwari and Troy 2015; Fleurence and Levine 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The use of supplements has been increasing worldwide in the last decades, even though the efficacy and safety of some of these products are still under discussion in the scientific community (Petroczi et al, 2011;Eudy et al, 2013;Cohen, 2012;Sepkowitz, 2013;Lachenmeier et al, 2013;Finley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An exemplarily overview how to filter out non-qualified studies following such an evidence-based review process is demonstrated in ▶ Fig. 1 [154].…”
Section: Proposal For a New Regulatory Frameworkmentioning
confidence: 99%